Yield, chemical composition, and efficiency of use of nitrogen by Marandu grass - Oliveira, Tadeu Silva de (2014)
The objective of this study was to evaluate the effect of five nitrogen doses on the productive and quality characteristics and the use efficiency of Brachiaria brizanthacv. Marandu grass. The treatments consisted of four doses of nitrogen (0, 60, 120, 180 and 240 kg ha-1), distributed through a completely randomized design with four replicates. Samples of the material were collected to analyze productivity variables, concentrations of neutral detergent fiber, crude protein and neutral detergent insoluble nitrogen, and in vitro dry matter digestibility. The nitrogen use efficiency, recovery of the applied nitrogen (RAN) and agronomic efficiency of the applied nitrogen (AE) were calculated. Dry mass production increased by 1,624.67 (kg/ha) as the nitrogen doses were increased. The doses of nitrogen affected the concentrations of neutral detergent fiber (from 294.6 to 381.4 g.kg-1, in the leaf), crude protein (from 86.1 to 99.6 g.kg-1, in the leaf) and neutral detergent insoluble protein (from 402.9 to 396.2 g.kg-1 CP, in the leaf). Nitrogen use efficiency increased, whereas RAN and AE were not affected by the nitrogen doses. Nitrogen fertilization promotes improvement in productivity and chemical composition of Marandu grass, also improving the efficiency with which the grass utilizes the nitrogen.